Corrosion behavior and mechanism of Cr and Cu alloy weathering steel in simulated marine atmospheric environment - Yin Chenghui; Zhang Xin; Wang Shuliu; Cheng Junhang; Zhang Hao; Yu Qiang; Xiao Kui (Journal of Materials Research and Technology)
This study developed a novel Cr and Cu alloyed weathering steel, Q345qENH steel, designed for coastal atmospheric environments. A comparative corrosion analysis was conducted between Q345qENH and Q345qd steel using various techniques, including metallography, corrosion kinetics, morphology observation, XRD, and electrochemical tests. Results show that Q345qENH exhibits superior corrosion resistance in simulated marine conditions compared to Q345qd, with the rust Layer Structure becoming more protective over time. The rust layer on Q345qENH forms a dual-layer structure, consisting of an inner Cr and Cu-rich layer and an outer γ-FeOOH/β-FeOOH layer. XRD analysis revealed an increasing α∗/γ∗ ratio over time. The corrosion mechanism indicates that Cr and Cu initially promote corrosion by forming oxides, but as corrosion progresses, Cr binds with α-FeOOH to form dense oxides like FeCr₂O₄ and α-(Fe, Cr)OOH, which protect the steel by limiting access to corrosive media.